Identity Transitions of Tapetum Phases: Insights into Vesicular Dynamics and in Mortem Support During Pollen Maturation - Gabriel Luis L. S. Moreira; Maria Eduarda P. Ferreira; Francisco S. Linhares (Plants)
Flower development progresses through twelve distinct stages, meticulously regulated to optimize plant reproductive success. At stage 5, the initiation of anther development occurs, which is further categorized into 14 stages divided into two defined phases: phase 1, known as microsporogenesis, and phase 2, termed microgametogenesis—encompassing pollen maturation and anther dehiscence. The maturation of pollen grains must be temporally synchronized with anther dehiscence, with auxin serving as a pivotal spatio-temporal link between these processes, coordinating various aspects of anther development, including stamen elongation, anther dehiscence, and tapetum development. The tapetum, a secretory tissue adjacent to the meiocytes, is essential for nurturing developing pollen grains by secreting components of the pollen wall and ultimately undergoing programmed cell death (PCD). This review primarily focuses on microgametogenesis, the identity and function of the tapetum during the different progression phases, the role of vesicular signaling in delivering external components crucial for pollen grain maturation, and the distinctive process of PCD associated with these developmental processes.